Isolated vitamin D supplementation improves the adipokine profile of postmenopausal women: a randomized clinical trial - Schmitt, Eneida B. [UNESP] (2023)
Objective: The aim of the study is to evaluate the effect of vitamin D supplementation alone on the adipokine profile of postmenopausal women. Methods: In this randomized clinical trial, 160 women were randomized to 2 groups: oral supplementation with 1,000 IU cholecalciferol/d (vitamin D, n = 80) or placebo (PL, n = 80). Women with amenorrhea 12 months or more and aged 50 to 65 years were included. Women with established cardiovascular disease, insulin-dependent diabetes, renal failure, liver diseases, and previous use of menopausal hormone therapy and vitamin D were excluded. The intervention lasted 9 months and serum adiponectin, resistin, and adipsin levels were determined at the start and end of treatment. Intention to treat was adopted as the statistical method using a repeated measures design, followed by Wald's multiple comparison test adjusted for group × time interaction. Results: After 9 months, 25-hydroxyvitamin D concentrations increased from 15.0 ± 7.5 to 27.5 ± 10.4 ng/mL (+45.4%) in the vitamin D group and decreased from 16.9 ± 6. to 13.8 ± 6.0 ng/mL (−18.5%) in the PL group (P < 0.001). In the vitamin D group, there was an increase in adiponectin (+18.6%) and a decrease in resistin (−32.4%, P < 0.05). At the end point, a difference was observed between the PL and vitamin D groups in mean adiponectin and resistin levels (11.5 ± 5.5 vs 18.5 ± 21.8 ng/mL, P = 0.047, and 16.5 ± 3.5 vs 11.7 ± 3.3 ng/mL, P = 0.027, respectively). There were no significant intervention effects on serum adipsin levels. Conclusions: Daily supplementation with 1,000 IU of vitamin D alone was associated with an increase in adiponectin and a decrease in resistin, suggesting a beneficial effect on the adipokine profile of postmenopausal women with vitamin D deficiency.